A Miniaturized Microstrip Antenna Array at 5G Millimeter-Wave Band - Shen, Xiumei; Liu, Yujia; Zhao, Luyu; Huang, Guan-Long; Shi, Xiaowei; Huang, Qiulin (IEEE antennas and wireless propagation letters, 2019)
A miniaturized two-element microstrip antenna array is proposed for the millimeter-wave band of fifth generation (5G) wireless communication systems. A surface of electromagnetic bandgap structures (EBG) is applied as the ground for two closely packed patch antennas operating in 5G New Radio (26 500-29 500 MHz) frequency band. With the help of the proposed EBG ground, the two E-shaped microstrip antenna elements can be placed in close proximity to each other by 0.3 wavelength center to center distance in free space at the center frequency, yet the mutual coupling between them can still reach to more than 23 dB within the whole band of interest, which is about 10 dB larger than that on normal ground. All major radiation characteristics of the two-element array are well reserved with the EBG ground. The proposed design can be used in multiple-input-multiple-output applications or as the building subarray of larger phased arrays at millimeter-wave bands for mobile communication systems.